Вміст MCPD-ефірів і ефірів гліцидолу в олійно-жирових продуктах - Демидова, Анастасія Олександрівна; Мольченко, Світлана Миколаївна; Левчук, Ірина Володимирівна; Носенко, Тамара Тихонівна (Національний університет харчових технологій, 2021)
The content of MCPD esters (MCPD-E) and glycidol esters (GE) in different types of fats and high-fat products was compared in this review. These substances have carcinogenic effects, genotoxicity, nephrotoxicity, suppress fertile function. The highest content of MCPD-E and GE is observed in palm oil, its fractions, margarine, fish oil and etc. Recent data on the toxicity of MCPD esters and glycidol esters have led to an understanding of the urgency of limiting their levels in food. It is expected that from January 1, 2021, the Codex Alimentarius Commission will adopt a new Code of Practice for the Prevention and Reduction of 3-MCPD-E and GE with the following restrictions on their content in fats: 1250 μg/kg for unrefined oils, refined coconut oil, maize, rapeseed, olives, sunflower, soybeans and palm kernels oils; 2500 μg/kg for other refined vegetable oils, fish oil and fats of other marine organisms. For vegetable oils and fats intended for infant formula the level of 750 μg/kg will be acceptable. Numerous studies showed that MPCs content exceeded in dietary fats. The majority of these toxic substances are consumed by the population with pastries, margarines and fried foods. The published data showed that although there were general dependences on the presence of certain levels of MCPD esters and glycidol esters in the same type of fat, it was not possible to determine the narrow ranges characteristic of one type of fat. An important factor in the formation of the increased content ofMCPD-esters and esters of glycidol is the conditions of cultivation of oilseeds, the conditions of their production and processing, which can differ significantly. The main influence on the formation of high levels of MCPD-E and GE has deodorization (or physical refining). Food processing such as frying, deep frying, baking bakery products, etc. do not change the content of MCPD-E and GE significantly (presumably due to the use oflower temperatures and longer process time).

Оглядова стаття присвячена порівнянню вмісту MCPD-ефірів (MCPD-Е) і ефірів гліцидолу (GE) в різноманітних жирах та gродуктах з високим вмістом жиру. Ці речовини проявляють канцерогенну дію, генотоксичність, нефротоксичність, пригнічують фертильну функцію. Найбільший вміст MCPD-Е та GE спостерігається в пальмовій олії, її фракціях, маргаринах, риб’ячому жирі тощо. Одержані за останні роки дані щодо токсичності MCPD-ефірів та ефірів гліцидолу призвели до розуміння терміновості обмеження їх вмісту в харчових продуктах. Очікується, що з 1 січня 2021 року Комісія Codex Alimentarius ухвалить новий Кодекс практики щодо запобігання та зменшення утворення 3-MCPD-E та GE з подальшим обмеженнями їх вмісту в жирах: 1250 мкг/кг для нерафінованих олій та рафінованої кокосової, кукурудзяної, ріпакової, оливкової, соняшникової, соєвої та пальмоядрової олії; 2500 мкг/кг для інших рафінованих рослинних олій, рибʼячого жиру та жирів інших морських організмів. Для рослинних олій і жирів, призначених для дитячого харчування, допустимий буде 750 мкг/кг. Численні дослідження показують перевищення цих ГДК у харчових жирах. Основну частину цих токсичних речовин населення споживає з випічкою, маргаринами та смаженими продуктами. У статті продемонстровано, що вміст MCPD-ефірів і ефірів гліцидолу в одному й тому ж виді жирів коливається в широкому діапазоні. Вагомими факторами формування MCPD-ефірів і ефірів гліцидолу є умови вирощування олійних, добування олії та переробки. Основний вплив на зростання вмісту MCPD-E та GE має дезодорування (або фізичне ра фінування жирів). Такі процеси обробки їжі, як її смаження, випічка хлібобулоч них виробів тощо не викликають суттєвого зростання вмісту MCPD-E та GE.
Content of MCPD-esters and glycidol esters in fat and oil products
Оглядова стаття
Keywords: MCPD-esters; MCPD-E; glycidol esters; vegetable oils; palm oil; margarine; MCPD-ефіри; ефіри гліцидолу; GE; рослинні олії; пальмова олія; маргарин